Assessing implicit and explicit dementia stigma in young adults and care-workers. (July 2020) - Kane, Alan; Murphy, Carol; Kelly, Michelle
This aim of this study was to assess implicit and self-reported stigma towards people with dementia in young adults with no contact or experience ( n = 23), and in care-workers ( n = 17 professional dementia care-workers). Data were analysed to determine whether stigma was related to self-reported levels of depression, anxiety, stress and professional burnout. Forty participants completed the Implicit Relational Assessment Procedure and Dementia Attitudes Scale. The Depression Anxiety and Stress Scale and Maslach Burnout Inventory were used to measure depression, anxiety, stress and professional burnout. The young adult group showed statistically significant levels of dementia stigma (on the two " dementia " trial-types, p = .027 and p = .030). Statistical analyses showed more dementia-positive attitudes in care-workers compared to young adults on the Implicit Relational Assessment Procedure and the Dementia Attitudes Scale (both p 's=.021). Spearman's Rho correlations tests showed that for the care-givers, higher levels of burn-out were associated with more negative attitudes towards people with dementia on both of the Dementia Attitudes Scale subscales (social comfort p <.001 and dementia knowledge p =.005). The results support prior research showing that experience with a stigmatised group can lower stigma and demonstrate the importance of providing a supportive work environment to mitigate burnout.